Experimental Ethnography Online. - Fortun, Kim; Fortun, Mike; Bigras, Erik; Saheb, Tahereh; Costelloe-Kuehn, Brandon; Crowder, Jerome; Price, Daniel; Kenner, Alison (Cultural Studies, 2014)
This essay describes The Asthma Files, an experimental, digital ethnography project structured to support a collaborative research process and new ways of presenting academic research. While examining ways in which asthma is understood, cared for and governed in varied settings, the project also examines how digital tools can be used to support new research practices, new ways of expressing ethnographic analyses and new ways of drawing readers to ethnographic work. The Asthma Files is an experiment in ethnography, and in science, health and environmental communication. The project responds to dramatic increases in asthma incidence in the USA and globally in recent decades, and to wide acknowledgement that new forms of asthma knowledges are needed. The project aims to advance understanding of the way asthma and other complex conditions can be productively engaged, leveraging ethnography, deep play with interdisciplinarity and deep respect for different kinds and forms of knowledges.